Fabrication and electrical characterization of Pd/TiO2/n-Si MIS structure using TiO2 film as insulator layer deposited by low temperature arc vapor deposition process - Shubham K.; Khan R.U.; Chakrabarti P. (My University, 2025)
Fabrication and electrical characterization of a Pd/TiO2/n-Si MIS structure have been reported in this paper. The TiO2 layer has been deposited on n-Si by using low temperature arc vapor deposition (LTAVD) technique. The current-voltage and capacitance-voltage characteristics were studied at room temperature (300 K) for sample devices with TiO2 film annealed at different temperatures (450 to 550°C). The study reveals that the capacitance in the accumulation region has frequency dispersion at high frequencies which is attributed to leakage behavior of TiO2 insulating layer, interface states and oxide defects. As-deposited film exhibits high level of interface states resulting in high leakage current density which can be reduced by an order of magnitude by post-deposition annealing. Different models of current conduction mechanism have been applied to study the measured data. It is found that Schottky-Richardson (SR) emission model is applicable at low bias voltage, Frenkel-Poole (FP) emission model at moderate bias voltages while Fowler-Nordheim (FN) tunneling dominates at higher bias voltages. Copyright © 2013 SPIE.